Intestinal obstruction in a rabbit: case study. Issue 6 (3rd June 2021) - Foreman, Emma
Abstract: Rabbits are complex animals with many requirements for them to thrive in the domestic environment. As prey animals, rabbits instinctively mask the signs of illness to avoid appearing vulnerable to predators. When they show signs of being unwell, it is likely that their condition is serious, and they should be presented to the veterinary surgeon promptly which was this case of a rabbit with an intestinal obstruction.